Why Do Girls in Rural China Have Lower School Enrollment? - Song, L; Appleton, S; Knight, J (2006)
Boys are more likely than girls to attend school in rural China. There is evidence that gender equity is a "luxury good"; the demand for female schooling is more income elastic than that for male schooling. Maternal education generally has a stronger effect on primary school enrollment and on educational expenditure than paternal education does. However, maternal education has a weaker effect on girls' enrollment in secondary school than paternal education does. There appears to be no monetary return to schooling for women, but a modest benefit for men. Households also appear to face a higher opportunity cost when enrolling young women than when enrolling young men.